Cytotoxicity New Insights into Toxic Assessment - Soloneski, Sonia; Larramendy, Marcelo L. (IntechOpen, 2021)
This edited book, Cytotoxicity - New Insights into Toxic Assessment, is intended to present some strategies, methods, interpretations and recent advances in order to facilitate scientific research on in vitro toxic responses, presenting both theoretical and practical aspects.